IDEAS OF SOLIDARITY AND TOLERANCE IN THE WORKS OF FARABIY AND BERUNIY (Scientific journal of the Fergana State University, 2023)
The article analyzed the importance of interpersonal ideas in the works of thinkers based on the principles of "Against the idea is only an idea, thought only against the thaught, against ignorance, enlightenment" in ensuring peace and stability in Uzbekistan.